A Flexible and Knittable Fiber Supercapacitor for Wearable Energy Storage with High Energy Density and Mechanical Robustness. Issue 7 (1st January 2018) - Liu, Qifan; Zang, Limin; Yang, Chao; Wei, Chun; Qiu, Jianhui; Liu, Chanjuan; Xu, Xu
Abstract : A flexible and knittable symmetric all-solid-state fiber supercapacitor (ASSFS) was fabricated by using two polypyrrole (PPy) microcone arrays coated stainless steel yarns (SSY) as fiber electrodes and current collectors. The microcone arrays and interconnected network structure of PPy could increase transport path for ions/electrons and enlarge the real contact area between PPy and electrolyte, leading to superior specific capacitance. In addition, the fiber electrode has a high tensile strength of ∼1200 MPa and elongation at break is 12.5%. The outstanding mechanical performance of the fiber electrode is attributed to the high mechanical properties of the SSY and the protection of PPy coating. The resultant ASSFS exhibits maximum specific capacitance of 42.7 F/cm 3, energy density of 3.8 mWh/cm 3 and power density of 388 mW/cm 3 (normalized to the whole device). The specific capacitance maintains 100% at different bending angles and 93.5% of its initial value after 1000 bending cycles. As a demonstration, a fabric and a bracelet knitted with five ASSFSs connected in series can light a LED.